Ceramic tile with stone luminosity and texture and preparation method thereof

By using materials such as imitation stone powder and high-temperature treatment, the limitations of traditional ceramic tile preparation methods in imitation stone effect, corrosion resistance and environmental protection are solved, and the gloss and texture of the stone on the surface of the ceramic tile is imitated, improving environmental protection performance and durability.

CN119707441AInactive Publication Date: 2025-03-28FOSHAN TUOBO BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411847077.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional ceramic tile preparation methods have limitations in the effect of imitating stones, corrosion resistance and environmental protection, and the chemical substances used may cause pollution to the environment.

Method used

Ceramic tiles are prepared through high-temperature treatment, washing and soaking, mixing, stirring, press forming, drying, firing and cooling processes.

Benefits of technology

The surface of the tiles has stone luster and texture, improves the aesthetics and decorative effect of the product, enhances the environmental protection performance and durability of the tiles, reduces the pollution to the environment, reduces the content of harmful substances, and extends the service life of the tiles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a ceramic tile with stone luminosity and texture and a preparation method thereof. According to the invention, the plant-based preservatives are derived from natural plant extracts, contain antibacterial and antifungal active ingredients, and can form a layer of protective film on the surface of the ceramic tile to effectively prevent the breeding of bacteria and molds, so that the service life of the ceramic tile is prolonged, and the characteristic is particularly important when the ceramic tile is used in a humid environment; and secondly, by adding the plant-based preservative, the overall environmental protection performance of the ceramic tile is improved, the influence on the environment is reduced, the requirement of the market for green building materials is met, and the market competitiveness of the product is enhanced. The application of the plant-based preservative can also reduce the dependence on traditional chemical preservatives, reduce the content of harmful substances in the ceramic tile, is beneficial to the health of consumers, and brings richer and more positive use experience to producers and consumers of the ceramic tile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tile preparation, in particular to a ceramic tile with stone luster and texture and a preparation method thereof. Background Art

[0002] Ceramic tile is a common building decoration material, which is mainly made of clay, quartz sand, feldspar and other raw materials through mixing, molding, high-temperature sintering and other processes. The traditional ceramic tile preparation technology mainly includes the following steps: Raw material preparation: Mix clay, quartz sand, feldspar and other raw materials to ensure the uniformity of the raw materials. Molding: The mixed raw materials are pressed and molded by a press to form a brick. Drying: The formed brick is dried to remove excess water. Sintering: The dried brick is sintered at high temperature to achieve the required hardness and strength. Cooling: The sintered brick needs to be cooled to prevent thermal cracking. Cutting and polishing: The sintered brick is cut into different sizes as needed and polished to enhance its gloss and decorativeness. Limitations of ceramic tiles. In the field of building materials, especially ceramic tile preparation technology, researchers have long been seeking a product that can imitate the gloss and texture of natural stone while having good physical properties and environmental protection characteristics.

[0003] However, although the traditional tile preparation method can produce decorative products, it has certain limitations in terms of stone imitation effects, corrosion resistance and environmental protection. The chemical substances used in the traditional tile preparation process may cause pollution to the environment, and some products contain substances that are harmful to the human body. Summary of the invention

[0004] The object of the present invention is to provide a ceramic tile having the luster and texture of stone and a preparation method thereof in order to solve the above-mentioned problems.

[0005] The technical solution adopted by the present invention is as follows: a ceramic tile with the luminosity and texture of stone, the ceramic tile comprising:

[0006] 350-500 parts by weight of imitation stone powder;

[0007] 250-300 parts by weight of high-quality clay;

[0008] 200-300 parts by weight of porcelain sand;

[0009] 100-200 parts by weight of special effect glaze;

[0010] Silane coupling agent 200-400 parts by weight;

[0011] 300-500 parts by weight of nano titanium dioxide;

[0012] 100-150 parts by weight of zinc phosphate;

[0013] 50-80 parts by weight of plant-based preservatives.

[0014] In a preferred embodiment, a ceramic tile having the luster and texture of stone and a method for preparing the same comprise the following steps:

[0015] S1: First weigh the raw materials for preparing tiles:

[0016] 350-500 parts by weight of imitation stone powder;

[0017] 250-300 parts by weight of high-quality clay;

[0018] 200-300 parts by weight of porcelain sand;

[0019] 100-200 parts by weight of special effect glaze;

[0020] Silane coupling agent 200-400 parts by weight;

[0021] 300-500 parts by weight of nano titanium dioxide;

[0022] 100-150 parts by weight of zinc phosphate;

[0023] 50-80 parts by weight of plant-based preservatives;

[0024] S2: High temperature treatment of the imitation stone powder to improve its bonding strength with the base material. Washing and soaking the clay to improve its plasticity;

[0025] S3: Mix the pretreated imitation stone powder, clay and porcelain sand in proportion, add silane coupling agent and nano titanium dioxide, and continue mixing to ensure uniform distribution;

[0026] S4: Add special effect glaze to the mixture and stir well to imitate the natural luster of the stone;

[0027] S5: pre-mixing and dissolving zinc phosphate and plant-based preservatives with a small amount of deionized water, and then adding them to the mixture;

[0028] S6: Add deionized water as needed to adjust the viscosity of the mixture to make it suitable for molding;

[0029] S7: Pressing the mixed material into a ceramic tile body of desired thickness through a pressing machine;

[0030] S8: Drying the formed tile embryo to remove excess water;

[0031] S9: sending the dried tile embryo into a kiln for firing, and the firing temperature and time are the process parameters for producing specific tiles;

[0032] S10: After the tiles are fired, they are cooled naturally to room temperature to prevent them from cracking due to excessive cooling;

[0033] S11: Inspection and packaging, conduct quality inspection on the cooled tiles, including appearance, size, strength, etc. Qualified products are packaged and marked with product specifications, models, production date and other information, and the entire process of producing tiles with stone luster and texture and their preparation is completed.

[0034] In a preferred embodiment, in step S1, the imitation stone powder can be made of one or a mixture of the following materials: marble powder, granite powder, limestone powder, quartz powder, dolomite powder, diatomaceous earth, talc powder, and calcite powder.

[0035] In a preferred embodiment, in step S1, the plant-based preservative comprises:

[0036] 40 parts by weight of zinc phosphate, 10 parts by weight of silane coupling agent, 15 parts by weight of nano silicon dioxide, 10 parts by weight of zinc oxide, 10 parts by weight of rosin extract, 10 parts by weight of citric acid extract, 10 parts by weight of camphor leaf extract, 5 parts by weight of biodegradable dispersant, and appropriate amount of deionized water;

[0037] The preparation method of the plant-based preservative comprises:

[0038] S1: Raw material preparation, prepare solid raw materials such as zinc phosphate, silane coupling agent, nano silicon dioxide, zinc oxide, etc. Rosin extract, citric acid extract, camphor leaf extract and biodegradable dispersant. Prepare deionized water.

[0039] S2: crushing and mixing, crushing zinc phosphate and zinc oxide to ensure that the powder fineness meets the requirements, and mixing the crushed powder with nano silicon dioxide.

[0040] S3: Dissolve the plant extract: dissolve the plant extract in an appropriate amount of deionized water and stir evenly.

[0041] S4: dissolving the silane coupling agent: dissolving the silane coupling agent in deionized water and stirring evenly.

[0042] S5: Mix the raw materials and add the dissolved plant extract solution and silane coupling agent solution to the powder mixture. Add the biodegradable dispersant and continue stirring to ensure that all ingredients are evenly dispersed.

[0043] S6: Adjust the viscosity. Deionized water may be added in an appropriate amount as needed to adjust the viscosity of the preservative so that it is suitable for the subsequent coating process.

[0044] S7: Filtration: filtering the mixed preservative solution through a filter to remove undissolved particles and impurities to obtain a plant-based preservative.

[0045] In a preferred embodiment, in step S2, the imitation stone powder needs to be treated in a high temperature furnace, the treatment temperature is set to 800°C to 1000°C, and the insulation time is 1 to 2 hours. This process is intended to remove organic impurities in the powder, improve its activity, and thus enhance its binding force with clay and porcelain sand. At the same time, the washing and soaking process of the clay should be carried out in water, the water temperature is controlled at 20°C to 30°C, and the soaking time is about 12 to 24 hours, so as to fully improve the plasticity of the clay and remove impurities.

[0046] In a preferred embodiment, in step S3, the mixing time is about 30 to 60 minutes to ensure that the various raw materials are fully mixed. The silane coupling agent and nano titanium dioxide are gradually added during the mixing process, and the mixing is continued for 10 to 15 minutes to ensure that they are evenly dispersed in the mixture.

[0047] In a preferred embodiment, in step S4, the special effect glaze includes: high gloss, semi-gloss, matte, frosted, metallic luster, crystallization, crackle, relief, wear-resistant, environmentally friendly, color-changing and transparent glaze; stir with a low-speed stirrer to avoid bubbles. The stirring time is about 15 to 20 minutes, until the glaze is completely and evenly distributed in the mixture, thereby imitating the natural luster of the stone;

[0048] In step S6, the water is added while stirring until the viscosity of the mixture reaches a suitable molding range, usually controlled at 2000 to 3000 cps. The amount of water added should be adjusted according to the water content of the raw materials and the ambient humidity.

[0049] In a preferred embodiment, in step S7, the mixed materials are fed into a pressing machine, and the applied pressure is controlled at 30 to 50 MPa to press the ceramic tile body of the desired thickness. The pressing time is about 30 seconds to 1 minute to ensure that the body structure is uniform and dense.

[0050] In step S8, the formed tile body is placed in a drying room, the drying temperature is controlled at 30°C to 60°C, the relative humidity is controlled at 40% to 60%, and the drying time is about 12 to 24 hours to remove excess moisture and prevent cracking during the firing process.

[0051] In a preferred embodiment, in step S9, the firing temperature is set between 1100° C. and 1250° C. according to the type of tile, and the firing time is about 45 to 90 minutes. The firing curve should be precisely controlled according to the specific requirements of the tile.

[0052] In a preferred embodiment, in step S10, the fired tiles need to be naturally cooled to 300°C to 500°C in the kiln, and then removed from the kiln to continue to be naturally cooled to room temperature. The entire cooling process is controlled within 6 to 12 hours to prevent the tiles from cracking due to excessive temperature differences.

[0053] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0054] 1. In the present invention, the plant-based preservatives are derived from natural plant extracts, which contain antibacterial and antifungal active ingredients and can form a protective film on the surface of the ceramic tile, effectively preventing the growth of bacteria and mold, thereby extending the service life of the ceramic tile. This feature is particularly important when used in a humid environment. Secondly, the addition of plant-based preservatives helps to improve the overall environmental performance of the ceramic tile, reduce the impact on the environment, meet the market demand for green building materials, and enhance the market competitiveness of the product.

[0055] 2. In the present invention, the application of plant-based preservatives can also reduce the dependence on traditional chemical preservatives, reduce the content of harmful substances in tiles, and benefit the health of consumers; finally, while improving the anti-corrosion performance of tiles, plant-based preservatives will not have an adverse effect on the gloss, texture and color of tiles. On the contrary, due to the characteristics of their natural ingredients, they may add a natural beauty to tiles. Plant-based preservatives can also give tiles better air permeability, help evaporate moisture inside tiles, and prevent deformation and damage caused by moisture accumulation; finally, the application of plant-based preservatives can also enhance the sensory experience of tiles. Due to its natural origin, it may bring a gentler and more natural touch and smell to tiles, thereby improving the comfort and satisfaction of users. In short, the introduction of plant-based preservatives not only enhances the practical performance of tiles, but also improves the overall quality and market value of the product, bringing a richer and more positive use experience to tile producers and consumers.

[0056] 3. In the present invention, through the use of imitation stone materials, the surface of the ceramic tile can present a texture and gloss similar to that of natural stone, which improves the aesthetics and decorative effect of the product and meets the consumer's demand for high-end decorative materials. The surface of the imitation stone ceramic tile has been specially treated and has strong pollution resistance, is easy to clean and maintain, and reduces the maintenance cost in daily use. The materials and production technologies used in the preparation process may be more environmentally friendly and reduce the burden on the environment. At the same time, the durability of the ceramic tile also means a lower replacement frequency, thereby saving resources. Imitation stone ceramic tiles can be produced in a variety of colors and textures to meet different design styles and personalized needs, providing designers with more creative space. Ceramic tiles with stone texture usually have good thermal stability, are not easy to expand and contract due to temperature changes, and are suitable for indoor and outdoor laying under various climatic conditions. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0058] Embodiment 1:

[0059] A ceramic tile with the luster and texture of stone, comprising:

[0060] 350 parts by weight of imitation stone powder;

[0061] 250 parts by weight of high-quality clay;

[0062] 200 parts by weight of porcelain sand;

[0063] 100 parts by weight of special effect glaze;

[0064] 200 parts by weight of silane coupling agent;

[0065] 300 parts by weight of nano titanium dioxide;

[0066] 100 parts by weight of zinc phosphate;

[0067] 50 parts by weight of plant-based preservatives.

[0068] The preparation method comprises the following steps:

[0069] S1: First weigh the raw materials for preparing tiles:

[0070] 350 parts by weight of imitation stone powder;

[0071] 250 parts by weight of high-quality clay;

[0072] 200 parts by weight of porcelain sand;

[0073] 100 parts by weight of special effect glaze;

[0074] 200 parts by weight of silane coupling agent;

[0075] 300 parts by weight of nano titanium dioxide;

[0076] 100 parts by weight of zinc phosphate;

[0077] 50 parts by weight of plant-based preservatives;

[0078] S2: High temperature treatment of the imitation stone powder to improve its bonding strength with the base material. Washing and soaking the clay to improve its plasticity;

[0079] S3: Mix the pretreated imitation stone powder, clay and porcelain sand in proportion, add silane coupling agent and nano titanium dioxide, and continue mixing to ensure uniform distribution;

[0080] S4: Add special effect glaze to the mixture and stir well to imitate the natural luster of the stone;

[0081] S5: pre-mixing and dissolving zinc phosphate and plant-based preservatives with a small amount of deionized water, and then adding them to the mixture;

[0082] S6: Add deionized water as needed to adjust the viscosity of the mixture to make it suitable for molding;

[0083] S7: Pressing the mixed material into a ceramic tile body of desired thickness through a pressing machine;

[0084] S8: Drying the formed tile embryo to remove excess water;

[0085] S9: sending the dried tile embryo into a kiln for firing, and the firing temperature and time are the process parameters for producing specific tiles;

[0086] S10: After the tiles are fired, they are cooled naturally to room temperature to prevent them from cracking due to excessive cooling;

[0087] S11: Inspection and packaging, conduct quality inspection on the cooled tiles, including appearance, size, strength, etc. Qualified products are packaged and marked with product specifications, models, production date and other information, and the entire process of producing tiles with stone luster and texture and their preparation is completed.

[0088] In the step S1, the imitation stone powder can be made of one or a mixture of the following materials: marble powder, granite powder, limestone powder, quartz powder, dolomite powder, diatomaceous earth, talcum powder, and calcite powder.

[0089] In step S1, the plant-based preservative comprises:

[0090] 40 parts by weight of zinc phosphate, 10 parts by weight of silane coupling agent, 15 parts by weight of nano silicon dioxide, 10 parts by weight of zinc oxide, 10 parts by weight of rosin extract, 10 parts by weight of citric acid extract, 10 parts by weight of camphor leaf extract, 5 parts by weight of biodegradable dispersant, and appropriate amount of deionized water;

[0091] The preparation method of the plant-based preservative comprises:

[0092] S1: Raw material preparation, prepare solid raw materials such as zinc phosphate, silane coupling agent, nano silicon dioxide, zinc oxide, etc. Rosin extract, citric acid extract, camphor leaf extract and biodegradable dispersant. Prepare deionized water.

[0093] S2: crushing and mixing, crushing zinc phosphate and zinc oxide to ensure that the powder fineness meets the requirements, and mixing the crushed powder with nano silicon dioxide.

[0094] S3: Dissolve the plant extract: dissolve the plant extract in an appropriate amount of deionized water and stir evenly.

[0095] S4: dissolving the silane coupling agent: dissolving the silane coupling agent in deionized water and stirring evenly.

[0096] S5: Mix the raw materials and add the dissolved plant extract solution and silane coupling agent solution to the powder mixture. Add the biodegradable dispersant and continue stirring to ensure that all ingredients are evenly dispersed.

[0097] S6: Adjust the viscosity. Deionized water may be added in an appropriate amount as needed to adjust the viscosity of the preservative so that it is suitable for the subsequent coating process.

[0098] S7: Filtration: filtering the mixed preservative solution through a filter to remove undissolved particles and impurities to obtain a plant-based preservative.

[0099] In step S2, the imitation stone powder needs to be treated in a high temperature furnace, the treatment temperature is set to 800°C to 1000°C, and the heat preservation time is 1 to 2 hours. This process is intended to remove organic impurities in the powder and improve its activity, thereby enhancing the binding force with clay and porcelain sand. At the same time, the washing and soaking process of the clay should be carried out in water, the water temperature is controlled at 20°C to 30°C, and the soaking time is about 12 to 24 hours, so as to fully improve the plasticity of the clay and remove impurities.

[0100] In step S3, the mixing time is about 30 to 60 minutes to ensure that the various raw materials are fully mixed. The silane coupling agent and nano titanium dioxide are gradually added during the mixing process, and the mixing is continued for 10 to 15 minutes to ensure that they are evenly dispersed in the mixture.

[0101] In step S4, the special effect glaze includes: high gloss, semi-gloss, matte, frosted, metallic gloss, crystallization, crackle, relief, wear-resistant, environmentally friendly, color-changing and transparent glaze; stirring with a low-speed stirrer to avoid bubbles. The stirring time is about 15 to 20 minutes, until the glaze is completely and evenly distributed in the mixture, thereby imitating the natural gloss of the stone;

[0102] In step S6, the water is added while stirring until the viscosity of the mixture reaches a suitable molding range, usually controlled at 2000 to 3000 cps. The amount of water added should be adjusted according to the water content of the raw materials and the ambient humidity.

[0103] In step S7, the mixed materials are fed into a pressing machine, and the applied pressure is controlled at 30 to 50 MPa to press the ceramic tile body of the required thickness. The pressing time is about 30 seconds to 1 minute to ensure that the body structure is uniform and dense.

[0104] In step S8, the formed tile body is placed in a drying room, the drying temperature is controlled at 30°C to 60°C, the relative humidity is controlled at 40% to 60%, and the drying time is about 12 to 24 hours to remove excess moisture and prevent cracking during the firing process.

[0105] In step S9, the firing temperature is set between 1100°C and 1250°C according to the type of tile, and the firing time is about 45 to 90 minutes. The firing curve should be precisely controlled according to the specific requirements of the tile;

[0106] In step S10, the fired tiles need to be naturally cooled to 300°C to 500°C in the kiln, and then removed from the kiln to continue to naturally cool to room temperature. The entire cooling process is controlled within 6 to 12 hours to prevent the tiles from cracking due to excessive temperature differences.

[0107] In the present invention, the plant-based preservatives are derived from natural plant extracts, which contain antibacterial and antifungal active ingredients and can form a protective film on the surface of the ceramic tile, effectively preventing the growth of bacteria and mold, thereby extending the service life of the ceramic tile. This feature is particularly important when used in a humid environment. Secondly, the addition of plant-based preservatives helps to improve the overall environmental performance of the ceramic tile, reduce the impact on the environment, meet the market demand for green building materials, and enhance the market competitiveness of the product.

[0108] In the present invention, the application of plant-based preservatives can also reduce the dependence on traditional chemical preservatives, reduce the content of harmful substances in tiles, and benefit the health of consumers; finally, while improving the anti-corrosion performance of tiles, plant-based preservatives will not have an adverse effect on the gloss, texture and color of tiles. Instead, due to the characteristics of their natural ingredients, they may add a natural beauty to tiles. Plant-based preservatives can also give tiles better air permeability, help evaporate moisture inside tiles, and prevent deformation and damage caused by moisture accumulation; finally, the application of plant-based preservatives can also enhance the sensory experience of tiles. Due to its natural origin, it may bring a gentler and more natural touch and smell to tiles, thereby improving the comfort and satisfaction of users. In short, the introduction of plant-based preservatives not only enhances the practical performance of tiles, but also improves the overall quality and market value of the product, bringing a richer and more positive use experience to tile producers and consumers.

[0109] In the present invention, through the use of imitation stone materials, the surface of the ceramic tile can present a texture and gloss similar to that of natural stone, thereby improving the aesthetics and decorative effect of the product and meeting the consumer's demand for high-end decorative materials. The surface of the imitation stone ceramic tile has been specially treated and has strong pollution resistance, is easy to clean and maintain, and reduces the maintenance cost in daily use. The materials and production technologies used in the preparation process may be more environmentally friendly and reduce the burden on the environment. At the same time, the durability of the ceramic tile also means a lower replacement frequency, thereby saving resources. Imitation stone ceramic tiles can be produced in a variety of colors and textures to meet different design styles and personalized needs, providing designers with more creative space. Ceramic tiles with stone texture usually have good thermal stability, are not easy to expand and contract due to temperature changes, and are suitable for indoor and outdoor laying under various climatic conditions.

[0110] Embodiment 2:

[0111] A ceramic tile with the luster and texture of stone, comprising:

[0112] Imitation stone powder ~ 500 parts by weight;

[0113] 300 parts by weight of high-quality clay;

[0114] 300 parts by weight of porcelain sand;

[0115] 200 parts by weight of special effect glaze;

[0116] 400 parts by weight of silane coupling agent;

[0117] 500 parts by weight of nano titanium dioxide;

[0118] 150 parts by weight of zinc phosphate;

[0119] 80 parts by weight of plant-based preservatives.

[0120] The preparation method comprises the following steps:

[0121] S1: First weigh the raw materials for preparing tiles:

[0122] Imitation stone powder ~ 500 parts by weight;

[0123] 300 parts by weight of high-quality clay;

[0124] 300 parts by weight of porcelain sand;

[0125] 200 parts by weight of special effect glaze;

[0126] 400 parts by weight of silane coupling agent;

[0127] 500 parts by weight of nano titanium dioxide;

[0128] 150 parts by weight of zinc phosphate;

[0129] 80 parts by weight of plant-based preservatives;

[0130] S2: High temperature treatment of the imitation stone powder to improve its bonding strength with the base material. Washing and soaking the clay to improve its plasticity;

[0131] S3: Mix the pretreated imitation stone powder, clay and porcelain sand in proportion, add silane coupling agent and nano titanium dioxide, and continue mixing to ensure uniform distribution;

[0132] S4: Add special effect glaze to the mixture and stir well to imitate the natural luster of the stone;

[0133] S5: pre-mixing and dissolving zinc phosphate and plant-based preservatives with a small amount of deionized water, and then adding them to the mixture;

[0134] S6: Add deionized water as needed to adjust the viscosity of the mixture to make it suitable for molding;

[0135] S7: Pressing the mixed material into a ceramic tile body of desired thickness through a pressing machine;

[0136] S8: Drying the formed tile embryo to remove excess water;

[0137] S9: sending the dried tile embryo into a kiln for firing, and the firing temperature and time are the process parameters for producing specific tiles;

[0138] S10: After the tiles are fired, they are cooled naturally to room temperature to prevent them from cracking due to excessive cooling;

[0139] S11: Inspection and packaging, conduct quality inspection on the cooled tiles, including appearance, size, strength, etc. Qualified products are packaged and marked with product specifications, models, production date and other information, and the entire process of producing tiles with stone luster and texture and their preparation is completed.

[0140] In the step S1, the imitation stone powder can be made of one or a mixture of the following materials: marble powder, granite powder, limestone powder, quartz powder, dolomite powder, diatomaceous earth, talcum powder, and calcite powder.

[0141] In step S1, the plant-based preservative comprises:

[0142] 40 parts by weight of zinc phosphate, 10 parts by weight of silane coupling agent, 15 parts by weight of nano silicon dioxide, 10 parts by weight of zinc oxide, 10 parts by weight of rosin extract, 10 parts by weight of citric acid extract, 10 parts by weight of camphor leaf extract, 5 parts by weight of biodegradable dispersant, and appropriate amount of deionized water;

[0143] The preparation method of the plant-based preservative comprises:

[0144] S1: Raw material preparation, prepare solid raw materials such as zinc phosphate, silane coupling agent, nano silicon dioxide, zinc oxide, etc. Rosin extract, citric acid extract, camphor leaf extract and biodegradable dispersant. Prepare deionized water.

[0145] S2: crushing and mixing, crushing zinc phosphate and zinc oxide to ensure that the powder fineness meets the requirements, and mixing the crushed powder with nano silicon dioxide.

[0146] S3: Dissolve the plant extract: dissolve the plant extract in an appropriate amount of deionized water and stir evenly.

[0147] S4: dissolving the silane coupling agent: dissolving the silane coupling agent in deionized water and stirring evenly.

[0148] S5: Mix the raw materials and add the dissolved plant extract solution and silane coupling agent solution to the powder mixture. Add the biodegradable dispersant and continue stirring to ensure that all ingredients are evenly dispersed.

[0149] S6: Adjust the viscosity. Deionized water may be added in an appropriate amount as needed to adjust the viscosity of the preservative so that it is suitable for the subsequent coating process.

[0150] S7: Filtration: filtering the mixed preservative solution through a filter to remove undissolved particles and impurities to obtain a plant-based preservative.

[0151] In step S2, the imitation stone powder needs to be treated in a high temperature furnace, the treatment temperature is set to 800°C to 1000°C, and the heat preservation time is 1 to 2 hours. This process is intended to remove organic impurities in the powder and improve its activity, thereby enhancing the binding force with clay and porcelain sand. At the same time, the washing and soaking process of the clay should be carried out in water, the water temperature is controlled at 20°C to 30°C, and the soaking time is about 12 to 24 hours, so as to fully improve the plasticity of the clay and remove impurities.

[0152] In step S3, the mixing time is about 30 to 60 minutes to ensure that the various raw materials are fully mixed. The silane coupling agent and nano titanium dioxide are gradually added during the mixing process, and the mixing is continued for 10 to 15 minutes to ensure that they are evenly dispersed in the mixture.

[0153] In step S4, the special effect glaze includes: high gloss, semi-gloss, matte, frosted, metallic gloss, crystallization, crackle, relief, wear-resistant, environmentally friendly, color-changing and transparent glaze; stirring with a low-speed stirrer to avoid bubbles. The stirring time is about 15 to 20 minutes, until the glaze is completely and evenly distributed in the mixture, thereby imitating the natural gloss of the stone;

[0154] In step S6, the water is added while stirring until the viscosity of the mixture reaches a suitable molding range, usually controlled at 2000 to 3000 cps. The amount of water added should be adjusted according to the water content of the raw materials and the ambient humidity.

[0155] In step S7, the mixed materials are fed into a pressing machine, and the applied pressure is controlled at 30 to 50 MPa to press the ceramic tile body of the required thickness. The pressing time is about 30 seconds to 1 minute to ensure that the body structure is uniform and dense.

[0156] In step S8, the formed tile body is placed in a drying room, the drying temperature is controlled at 30°C to 60°C, the relative humidity is controlled at 40% to 60%, and the drying time is about 12 to 24 hours to remove excess moisture and prevent cracking during the firing process.

[0157] In step S9, the firing temperature is set between 1100°C and 1250°C according to the type of tile, and the firing time is about 45 to 90 minutes. The firing curve should be precisely controlled according to the specific requirements of the tile;

[0158] In step S10, the fired tiles need to be naturally cooled to 300°C to 500°C in the kiln, and then removed from the kiln to continue to naturally cool to room temperature. The entire cooling process is controlled within 6 to 12 hours to prevent the tiles from cracking due to excessive temperature differences.

[0159] In the present invention, the plant-based preservatives are derived from natural plant extracts, which contain antibacterial and antifungal active ingredients and can form a protective film on the surface of the ceramic tile, effectively preventing the growth of bacteria and mold, thereby extending the service life of the ceramic tile. This feature is particularly important when used in a humid environment. Secondly, the addition of plant-based preservatives helps to improve the overall environmental performance of the ceramic tile, reduce the impact on the environment, meet the market demand for green building materials, and enhance the market competitiveness of the product.

[0160] In the present invention, the application of plant-based preservatives can also reduce the dependence on traditional chemical preservatives, reduce the content of harmful substances in tiles, and benefit the health of consumers; finally, while improving the anti-corrosion performance of tiles, plant-based preservatives will not have an adverse effect on the gloss, texture and color of tiles. Instead, due to the characteristics of their natural ingredients, they may add a natural beauty to tiles. Plant-based preservatives can also give tiles better air permeability, help evaporate moisture inside tiles, and prevent deformation and damage caused by moisture accumulation; finally, the application of plant-based preservatives can also enhance the sensory experience of tiles. Due to its natural origin, it may bring a gentler and more natural touch and smell to tiles, thereby improving the comfort and satisfaction of users. In short, the introduction of plant-based preservatives not only enhances the practical performance of tiles, but also improves the overall quality and market value of the product, bringing a richer and more positive use experience to tile producers and consumers.

[0161] In the present invention, through the use of imitation stone materials, the surface of the ceramic tile can present a texture and gloss similar to that of natural stone, thereby improving the aesthetics and decorative effect of the product and meeting the consumer's demand for high-end decorative materials. The surface of the imitation stone ceramic tile has been specially treated and has strong pollution resistance, is easy to clean and maintain, and reduces the maintenance cost in daily use. The materials and production technologies used in the preparation process may be more environmentally friendly and reduce the burden on the environment. At the same time, the durability of the ceramic tile also means a lower replacement frequency, thereby saving resources. Imitation stone ceramic tiles can be produced in a variety of colors and textures to meet different design styles and personalized needs, providing designers with more creative space. Ceramic tiles with stone texture usually have good thermal stability, are not easy to expand and contract due to temperature changes, and are suitable for indoor and outdoor laying under various climatic conditions.

[0162] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0163] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramic tile with the luminosity and texture of stone, characterized by: The tiles include: 350-500 parts by weight of imitation stone powder; 250-300 parts by weight of high-quality clay; 200-300 parts by weight of porcelain sand; 100-200 parts by weight of special effect glaze; Silane coupling agent 200-400 parts by weight; 300-500 parts by weight of nano titanium dioxide; 100-150 parts by weight of zinc phosphate; 50-80 parts by weight of plant-based preservatives.

2. A ceramic tile with stone luster and texture and a preparation method thereof as claimed in claim 1, characterized in that: The preparation method comprises the following steps: S1: First weigh the raw materials for preparing tiles: 350-500 parts by weight of imitation stone powder; 250-300 parts by weight of high-quality clay; 200-300 parts by weight of porcelain sand; 100-200 parts by weight of special effect glaze; Silane coupling agent 200-400 parts by weight; 300-500 parts by weight of nano titanium dioxide; 100-150 parts by weight of zinc phosphate; 50-80 parts by weight of plant-based preservatives; S2: subjecting the imitation stone powder to high temperature treatment to improve its bonding strength with the base material; and washing and soaking the clay to improve its plasticity; S3: Mix the pretreated imitation stone powder, clay and porcelain sand in proportion, add silane coupling agent and nano titanium dioxide, and continue mixing to ensure uniform distribution; S4: Add special effect glaze to the mixture and stir well to imitate the natural luster of the stone; S5: pre-dissolve the zinc phosphate and the plant-based preservative with a small amount of deionized water, and then add them to the mixture; S6: Add deionized water as needed to adjust the viscosity of the mixture to make it suitable for molding; S7: Pressing the mixed material into a ceramic tile body of desired thickness through a pressing machine; S8: Drying the formed tile embryo to remove excess water; S9: sending the dried tile embryo into a kiln for firing, and the firing temperature and time are the process parameters for producing specific tiles; S10: After the tiles are fired, they are cooled naturally to room temperature to prevent cracking of the tiles due to excessive cooling; S11: Inspection and packaging: conduct quality inspection on the cooled tiles, including appearance, size, and strength; package qualified products, and mark product specifications, models, and production date information, thus completing the entire process of producing tiles with stone luster and texture and their preparation.

3. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In the step S1, the imitation stone powder can be made of one or a mixture of the following materials: marble powder, granite powder, limestone powder, quartz powder, dolomite powder, diatomaceous earth, talcum powder, and calcite powder.

4. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S1, the plant-based preservative includes: 40 parts by weight of zinc phosphate, 10 parts by weight of silane coupling agent, 15 parts by weight of nano silicon dioxide, 10 parts by weight of zinc oxide, 10 parts by weight of rosin extract, 10 parts by weight of citric acid extract, 10 parts by weight of camphor leaf extract, 5 parts by weight of biodegradable dispersant, and appropriate amount of deionized water; The preparation method of the plant-based preservative comprises: SA-1: Raw material preparation, including zinc phosphate, silane coupling agent, nano-silica, zinc oxide solid raw materials; rosin extract, citric acid extract, camphor leaf extract and biodegradable dispersant; deionized water; SA-2: Crushing and mixing: crush zinc phosphate and zinc oxide to ensure that the powder fineness meets the requirements; mix the crushed powder with nano-silicon dioxide evenly; 3: Dissolve the plant extract: dissolve the plant extract in an appropriate amount of deionized water and stir evenly; SA-4: Dissolve the silane coupling agent in deionized water and stir evenly; SA-5: Mix the raw materials and add the dissolved plant extract solution and silane coupling agent solution to the powder mixture; add the biodegradable dispersant and continue stirring to ensure that all ingredients are evenly dispersed; SA-6: Adjust the viscosity. Deionized water can be added as needed to adjust the viscosity of the preservative to make it suitable for the subsequent application process; SA-7: Filtration: Filter the mixed preservative solution through a filter to remove undissolved particles and impurities to obtain a plant-based preservative.

5. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S2, the imitation stone powder needs to be treated in a high-temperature furnace, the treatment temperature is set to 800°C to 1000°C, and the insulation time is 1 to 2 hours; this process is intended to remove organic impurities in the powder and improve its activity, thereby enhancing the binding force with clay and porcelain sand; at the same time, the washing and soaking process of the clay should be carried out in water, the water temperature is controlled at 20°C to 30°C, and the soaking time is about 12 to 24 hours, so as to fully improve the plasticity of the clay and remove impurities.

6. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S3, the mixing time is about 30 to 60 minutes to ensure that the various raw materials are fully mixed; the silane coupling agent and nano titanium dioxide are gradually added during the mixing process, and the mixing is continued for 10 to 15 minutes to ensure that they are evenly dispersed in the mixture.

7. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S4, the special effect glaze includes: high gloss, semi-gloss, matte, frosted, metallic gloss, crystallization, crackle, relief, wear-resistant, environmentally friendly, color-changing and transparent glaze; stirring with a low-speed stirrer to avoid generating bubbles; stirring for about 15 to 20 minutes until the glaze is completely and evenly distributed in the mixture, thereby imitating the natural gloss of the stone; In step S6, water is added while stirring until the viscosity of the mixture reaches a suitable molding range, usually controlled at 2000 to 3000 cps; the amount of water added should be adjusted according to the water content of the raw materials and the ambient humidity.

8. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S7, the mixed material is fed into a pressing machine, and the applied pressure is controlled at 30 to 50 MPa to press the ceramic tile body into a desired thickness; the pressing time is about 30 seconds to 1 minute to ensure that the body structure is uniform and dense; In step S8, the formed tile body is placed in a drying room, the drying temperature is controlled at 30°C to 60°C, the relative humidity is controlled at 40% to 60%, and the drying time is about 12 to 24 hours to remove excess moisture and prevent cracking during the firing process.

9. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S9, the firing temperature is set between 1100° C. and 1250° C. according to the type of tile, and the firing time is about 45 to 90 minutes; the firing curve should be accurately controlled according to the specific requirements of the tile.

10. A ceramic tile with stone luster and texture and a method for preparing the same as claimed in claim 2, characterized in that: In step S10, the fired tiles need to be naturally cooled to 300°C to 500°C in the kiln, and then removed from the kiln to continue to be naturally cooled to room temperature; the entire cooling process is controlled within 6 to 12 hours to prevent the tiles from cracking due to excessive temperature differences.